PHYTO-ASSISTED SYNTHESIS OF GOLD NANOPARTICLES BY AQUEOUS EXTRACT OF Curcuma longa and THE EVALUATION OF TOTAL PHENOLIC AND FLAVONOID CONTENTS - DHANYARAJ, D.; THOMAS, AKHILA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Growing low cost and eco-friendly methods for metallic nanoparticles is a growing need. Using plants towards synthesis of nanoparticles are beneficial with the presence of bio-molecules in plants, which can act as capping/stabilizing and reducing agents. In the present study we describe rapid biosynthesis of gold nanoparticles by Curcuma longa aqueous extract. Synthesized nanoparticles were characterized by UV–Visible spectroscopy, transmission electron microscopy (TEM) and the chemical groups in plant extract were detected by Fourier Transform Infra-Red (FT-IR) spectroscopy. TEM study showed that the mean diameter and standard deviation for the silver nanoparticles were 14.12 ± 8.26 nm. Total phenolic and flavonoid contents and radical scavenging activity of the aqueous extract and GNPs/extract mixture, were also evaluated in this study. It can be concluded that the rhizome of C. longa is a good source of phenolic compounds, a potent antioxidant and a valuable choice for bio-reduction and biosynthesis of gold.